2012
DOI: 10.3390/md10030604
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxantin: A Treasure from the Sea

Abstract: The World Health Organization (WHO) estimates that 2.3 billion people will be overweight and 700 million obese in 2015. The reasons for this disastrous trend are attributed to the global tendency toward the reduced magnitude of exercise and physical activity and the increased dietary intake of fats, sugars and calories with reduced amount of vitamins and minerals. To prevent life-style-related diseases, like Metabolic Syndrome (MS), researchers’ attention is increasingly focusing on some of the so called “func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
168
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(184 citation statements)
references
References 55 publications
2
168
0
6
Order By: Relevance
“…The extracts of D. dichotoma, A. multifida, C. cupressoides, and S. vulgare were found to have the highest TPC values (p < 0.05), while the seaweeds C. crenulata and U. fasciata had the lowest ones. High levels of TPC in brown marine algae are expected, considering reports indicating they are rich sources in fucoxanthin (D'Orazio et al, 2012) and phlorotannins (Wang et al, 2012). Similar results were also described by Wang et al (2009) (Vinayak, Sabu, & Chatterji, 2011), whose values were very similar to the methanolic extracts from the brown seaweeds D. dichotoma and S. vulgare analyzed in this study.…”
Section: Tpc Valuessupporting
confidence: 75%
“…The extracts of D. dichotoma, A. multifida, C. cupressoides, and S. vulgare were found to have the highest TPC values (p < 0.05), while the seaweeds C. crenulata and U. fasciata had the lowest ones. High levels of TPC in brown marine algae are expected, considering reports indicating they are rich sources in fucoxanthin (D'Orazio et al, 2012) and phlorotannins (Wang et al, 2012). Similar results were also described by Wang et al (2009) (Vinayak, Sabu, & Chatterji, 2011), whose values were very similar to the methanolic extracts from the brown seaweeds D. dichotoma and S. vulgare analyzed in this study.…”
Section: Tpc Valuessupporting
confidence: 75%
“…A stepwise approach to maximizing the benefits from seaweed aquaculture would include to sequentially extract high-value molecules used in the food, pharma or biotech industries, such as bioactive sulphated polysaccharides, pigments, and antioxidants (D'Orazio et al, 2012;Mak et al, 2014;Herrero and Ibáñez, 2015), and then convert-after extraction of carbohydrates for the hydrocollid industry or for biofuels production-the lowervalue residue to protein concentrates with value in the feed industry (Francavilla et al, 2015;Bikker et al, 2016;Seghetta et al, 2016). Algal biorefineries have evolved from concept and laboratory tests to pilot-scale plants involving a range of seaweed species and environments (e.g., Baghel et al, 2014;Lorbeer et al, 2015;Bikker et al, 2016;Masarin et al, 2016), and may soon become commercial operations.…”
Section: Global Seaweed Production and The Associated Co 2 Uptakementioning
confidence: 99%
“…Worldwide, there is an increasing importance given to learn more about seaweeds for their diverse biological activities such as antiinflammatory, antimicrobial and anticancer [5,[7][8][9]11,15,[17][18][19][20] and the importance of some species of marine in food diet [9,21,22] as well as their contributionin pharmaceutical, drug development and food processing fields [3,14,20,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Seaweeds have become particularly interesting and many studies have been conducted to characterize their contents which have shown great potential in a wide range of biological activities such as antiinflammatory, anticoagulant, anti-obesity, antibacterial, antiviral, antifungal, antioxidant, antitumoral, antiproliferative [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%